Evaluation of soil quality in different reclamation areas of Hequ open-pit mine dump - Zhao Hongbao; Jiang Dongmei; Li Yue; Cheng Hui; Wu Tong (矿业科学学报, 2023)
The open-pit mine has high mining efficiency, low cost, safe production and good economic benefits, but it also affects the structure and physical and chemical properties of the soil in the dump, resulting in the loss of soil nutrients and damage to land resources to a certain extent.Based on the nonlinear membership function method and the improved Nemero index evaluation method, five nutrient indexes were selected to comprehensively evaluate the soil fertility quality of Hequ open-pit mine.The research shows that the soil fertility quality index of different reclamation areas in Hequ open-pit mine is ranked as below 4(0.453)>1(0.447)>2(0.402)>3(0.213)>up 4(0.139), that is, the soil quality level of reclaimed area is higher than that of unreclaimed area.On the whole, the soil quality was at the lower or poor level, and the main limiting factors were organic matter, alkali-hydrolyzed nitrogen, available phosphorus, and soil pH.The results of this study can provide reference for soil improvement, soil fertility improvement and soil sustainable utilization in this area.for soil improvement, soil fertility improvement and soil sustainable utilization in this area.